1998
DOI: 10.1161/01.atv.18.9.1386
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Frequently Colocalizes With the Terminal Complement Complex in the Intima of Early Atherosclerotic Lesions of Human Coronary Arteries

Abstract: Abstract-There is increasing evidence that complement activation may play a role in atherogenesis. Complement proteins have been demonstrated to be present in early atherosclerotic lesions of animals and humans, and cholesterol-induced atherosclerotic lesion formation is reduced in complement-deficient animals. Potential complement activators in atherosclerotic lesions are now a subject matter of debate. C-reactive protein (CRP) is an acute-phase protein that is involved in inflammatory processes in numerous w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
317
1
15

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 484 publications
(344 citation statements)
references
References 29 publications
8
317
1
15
Order By: Relevance
“…It is well known, however, that most of the CRP within atherosclerotic lesions derives from plasma CRP insudation 24. We therefore performed extensive immunohistochemical studies using a well‐established mouse monoclonal anti‐CRP antibody 12, 13, 24, 25. Surprisingly, besides increasing extracellular staining around calcified areas of grade 2 to 4 lesions (rather impressive in grade 4 lesions) as well as rare intracellular staining, we were not able to detect any extracellular staining in early lesions (Figure 5B, left panels).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known, however, that most of the CRP within atherosclerotic lesions derives from plasma CRP insudation 24. We therefore performed extensive immunohistochemical studies using a well‐established mouse monoclonal anti‐CRP antibody 12, 13, 24, 25. Surprisingly, besides increasing extracellular staining around calcified areas of grade 2 to 4 lesions (rather impressive in grade 4 lesions) as well as rare intracellular staining, we were not able to detect any extracellular staining in early lesions (Figure 5B, left panels).…”
Section: Resultsmentioning
confidence: 99%
“…This question, in turn, focuses attention on the possibility that CRP itself might contribute to atherothrombosis. CRP selectively binds to LDL, especially the modified LDL found within atherosclerotic plaques, 30 and CRP is present almost universally in the plaques, 31 colocalized with both modified LDL and activated complement. 30 The binding of CRP to ligands, including modified LDL, activates complement and could be pro-inflammatory and contribute to atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Torzewski et al 30 have reported that CRP deposited in the arterial wall in early atherosclerosis activates a complement protein, which might cause Figure 1 Adjusted means of baPWV compared among quartiles of (a) CRP, (b) UA, and (c) estimated GFR in male subjects (adjusted for age, BMI, systolic blood pressure, HR, TC, HDL, FBS, log TG, UA (except for analysis of the quartile UA), estimated GFR (except for analysis of the quartile estimated GFR), log CRP (except for analysis of the quartile CRP), smoking status, alcohol consumption, frequency of exercise, hyperlipidemia, and diabetes). Figure 2 Adjusted means of baPWV compared among quartiles of (a) CRP, (b) UA, and (c) estimated GFR in female subjects (adjusted for age, BMI, systolic blood pressure, HR, TC, HDL, FBS, log TG, UA (except for analysis of the quartile UA), estimated GFR (except for analysis of the quartile estimated GFR), log CRP (except for analysis of the quartile CRP), smoking status, alcohol consumption, frequency of exercise, hyperlipidemia, diabetes, and menopausal status).…”
Section: Discussionmentioning
confidence: 99%